Relasi Suami Istri pada Pasangan Nikah Usia Dini di Wilayah Bukit Batu Bengkalis: Perspektif Hukum Keluarga Islam - Mahyarahila; Kasmidin; Arisman (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of early-age marriage remains prevalent, particularly in the Bukit Batu area of Bengkalis. Marriage is often considered problematic because the individuals involved typically adolescents are not yet mentally or emotionally mature and remain economically and psychologically dependent on their parents. Adolescence should ideally be a golden period for acquiring knowledge and shaping one's identity through both formal and non-formal education. A lack of preparedness for married life affects the relationship between husband and wife, leading to issues such as poor communication, emotional instability, limited knowledge of reproductive health, and unpreparedness to handle household responsibilities all of which increase the risk of domestic violence. This study aims to examine the husband-wife relationship among early-married couples in the area, identify indicators of their relationship quality, and analyze it from the perspective of Islamic Family Law. The research method used is field research with a qualitative descriptive approach. The findings indicate that early-married couples face various challenges—emotional, social, and economic. Indicators of a healthy relationship include open and honest communication, emotional maturity, independence, responsibility, emotional support, and healthy conflict resolution. From the perspective of Islamic Family Law, the husband-wife relationship should be built on the principles of equality, cooperation, and a balance between rights and obligations. Therefore, a tailored educational and mentoring approach is necessary for early-married couples to help them live a harmonious and responsible married life.